Correlation of cutaneous manifestations with body mass index, blood glucose, and hormonal levels in patients with polycystic ovarian disease - Yugal K Sharma; Shivanti Chauhan; Pallavi Singh; Kirti Deo (Wolters Kluwer Medknow Publications, 2020)
Background: Polycystic ovarian disease (PCOD) is characterized by oligo/anovulation, ultrasonographic evidence of polycystic ovaries and cutaneous features such as hirsutism, acne, acanthosis nigricans, androgentic alopecia, and signs of virilization. Aim: Correlation of dermatological manifestations with body mass index (BMI), blood glucose, and levels of free testosterone, dehydroepiandrosterone sulfate (DHEAS), follicle stimulating hormone (FSH), and luteinizing hormone (LH) in patients of PCOD hailing from Pimpri, Pune. Subjects and Methods: This observational study was carried out from November 2015-April 2017 on 102 patients (aged 12-45 years, non-pregnant) of PCOD, attending dermatology/gynecology outpatient departments. After recording socio-demographic/menstrual and medical history, BMI was calculated and examination of cutaneous manifestations were done. Participants were then subjected to pelvic ultrasonography and blood sugar/hormonal estimation. Statistical Analysis: By using statistical package for the Social Sciences 17.0 software, Chi-square test, and Fisher's exact test. Results: Age: 59.80% belonged to the third decade (range,12-40; mean, 26.27 ± 5.05 years); ultrasonography revealed polycystic ovaries in 79.41%. Cutaneous manifestations recorded were - acne (74.50%); acanthosis nigricans (50%); striae (49.02%); hirsutism (40.19%); acrochordons (36.27%); seborrheic dermatitis (32.35%), and androgenetic alopecia (30.39%). Free testosterone (35;34.31%), DHEAS (9;8.82%), LH and FSH (2;1.96% each), and LH: FSH ratio (51;50%) were raised. Statistical association of acanthosis nigricans emerged with free testosterone (P = 0.034), DHEAS (P = 0.016), fasting blood sugar (P = 0.01), and raised BMI (P = 0.002) and of hirsutism with raised DHEAS (P = 0.016), free testosterone (P = 0.012), and BMI (P = 0.022). Conclusion: Significant correlations demonstrated were acanthosis nigricans with free testosterone, DHEAS, FBS, and BMI and hirsutism with DHEAS, free testosterone, and BMI.